Recent Trends in Screening of Oral Cancer - Dr. Pooja Kabra; Dr.R. Roghini; Dr. Somenath Ghosh; Dr. Sucheta Karande; Dr. M. Chandran; Dr. Abikesh Prasada Kumar Mahapatra (International Journal of Pharma and Bio Sciences, 2024)
This Review focuses on the pressing global healthcare concerns surrounding the high prevalence of oral carcinoma and its late-stage detection. The World Health Organization (WHO) prioritizes early diagnosis and prevention of oral cancer, emphasizing the significance of timely oral screenings for understanding disease prognosis. Detecting crucial signs and symptoms during initial oral screening significantly enhances patient survival rates. Contributing factors to elevated mortality and morbidity include socio-economic elements, insufficient public awareness, as well as basic medical shortages. While visual examination is conventionally employed to In the presence of risk factors, keep track of client survival, its clinical utility is limited. To address this, efficient screening tools are needed to differentiate between benign and malignant lesions, providing early information about oral squamous cell carcinoma (OSCC). Optical imaging techniques such as tissue-fluorescence imaging and optical coherence tomography show promise. Oral cancer ranks as the sixth most frequent cancer globally, primarily oral squamous cell carcinoma. Detection methods include comprehensive clinical examinations, costly biochemical tests, and invasive biopsies. Saliva emerges as a noninvasive, promising diagnostic fluid for early oral cancer detection. This Review emphasizes its potential, containing a variety of biomarkers (DNA, RNA, and protein indicators) that help with early diagnosis. Direct contact with oral cancer lesions improves the specificity and sensitivity of saliva for screening. Numerous salivary biomarkers have been found, including defensin-1, P53, and cells (IL-8, IL-1b, and TNF-a). However, further research is needed for clinical validation. Late-stage oral cancer diagnosis contributes to elevated mortality rates. Early detection and treatment remain crucial for improved patient outcomes. Spectroscopy, salivary proteomics, toluidine blue staining, auto fluorescence, brush biopsy, DNA analysis, and biomarkers are a few noninvasive techniques that show potential. Nanotechnology-based detection systems, utilizing nanoparticles, offer highly sensitive and specific diagnostic techniques, potentially revolutionizing oral cancer management.